Pictures Of Remote Metastasis In Patients Naspharyngeal Carcinoma In RSUP. H. Adam Malik Medan For The Period Of 2014-2016 - Namira Friliandita (Institute of Computer Science (IOCS), 2020)
Other malignant ENT tumors in Indonesia. NPC is one of the five superior malignant tumors with the highest frequency (altogether with cervical cancer, breast tumor, lymph node tumor and skin tumor). Meanwhile, leading in the first place are the tumors in the head and neck region. Objectives. To know the characteristics of distant metastases in nasopharyngeal carcinoma patients in Haji Adam Malik General Hospital in Medan during 2014-2016 period. Methods. The population in this study is nasopharyngeal carcinoma patients in Haji Adam Malik General Hospital with total sampling as the sampling technique. This study is a descriptive study using cross-sectional design retrospective, and the technique used for collecting data by using secondary data from medical records. Results. (4.7%) had lung metastases, 10 patients (4.7%) had cardiac dysfunction, and others (0.9%). Conclusion. The biggest amount of patients was found in the age group of 38-47 years, mostly men with last education was high school, stage IV, and the most common damaged organ was liver.